United Nations Office on Drugs and Crime's Efforts to Prevent the Distribution of Synthetic Drugs in Southeast Asia: through the Regional Frameworks Programme 2022-2026 - Nurdiansyah, Muhammad Rizki Dwi; Siregar, Wahidah Zein Br (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This study describes UNODC's efforts to prevent the circulation of synthetic drugs in Southeast Asia. This study was conducted to determine what efforts UNODC, as an international organization, has made to address the high number of synthetic drug trafficking cases in Southeast Asia. This study used a descriptive qualitative method. Data for this study were collected through document analysis. The results of this study indicate that UNODC has made efforts to prevent synthetic drug trafficking in Southeast Asia. This effort is carried out through the Regional Frameworks Programme 2022-2026, which includes programs such as the Mekong Memorandum of Understanding on Drug Control, the ASEAN Ministerial Meeting on Drug Matters, and the ASEAN Senior Officials Meeting on Drug Matters. This study underscores the importance of UNODC in regional cooperation to prevent synthetic drug trafficking.